ANALISIS USAHA PURSE SEINE DI KECAMATAN JUWANA KABUPATEN PATI - Mochammad T.S. Utomo; Suparjo S. Djasmani; Hery Saksono; Suadi Suadi (Universitas Gadjah Mada, 2013)
The research aimed to analyze ﬁ sh catch, income, cost, and proﬁt of purse seine ﬁsheries in Juwana. Survey was conducted on 29 (twenty nine) purse seine owners as respondents, consisting of one mini purse seiners, ﬁve medium purse seiners, and 23 (twenty three) large purse seiners. All of them were interviewed by using questioners. The study showed that average total income per year was Rp1,603,020,400 for the large purse seiners, Rp924,444,000 for medium purse seiners, and Rp1,040,000,000 for mini purse seiners. The average of expense per year was Rp1,362,482,800 for the large purse seiners, Rp912,084,700 for the medium purse seiners, and Rp1,009,650,100 for the mini purse seiners consisting of ﬁxed cost and total variable cost. The average ﬁxed cost of big purse seiners is in amount of 17.5% from total cost (Rp238,392,800), the medium purse seiners is 19.8% (Rp. 180.578.100) and for the mini purse seiners is in amount of 14,8% (Rp149.750.100). The average of total variable cost from the total cost per year was in amount of 82.5% (Rp1.124.090.000) for the large purse seiners, 80.2% for the medium purse seiners (Rp731.506.600), and 85.2% for the mini purse seiners (Rp799.900.000). The net proﬁt were Rp240.537.500 for large purse seiners, Rp12.359.600 for medium purse seiners, and Rp30.349.800 for mini purse seiners, respectively. The study showed that the Renevue-Cost Ratio is more than one, and there fore, purse seine businesses in Juwana generally are feasible to be developed. The purse seiners which were equiped with freezer technology generated higher net proﬁt than others.